The systematic status of two enigmatic ocypodoid crabs, "Paracleistostoma" dentatum Tesch, 1918, and "Paracleistostoma" fossulum Barnard, 1955 (Crustacea: Decapoda: Brachyura) - Ng, Peter K.l. (Zootaxa, 2012)
The systematic positions of two ocypodoid crabs, Paracleistostoma dentatum Tesch, 1918, and P. fossulum Barnard, 1955,have been uncertain because each were described from single female specimens, with Ng et al. (2008) referring them pro-visionally to the Dotillidae and Varunidae, respectively. Števčić (2011) recently established two new genera, Lazarocleis-tostoma Števčić, 2011, and Brankocleistostoma Števčić, 2011, for P. dentatum Tesch, 1918, and P. fossulum Barnard,1955, respectively. He also recognised two new families, Lazarocleistostomidae Števčić, 2011, and Brankocleistostomi-dae Števčić, 2011, for these genera. Examination of the types and fresh material of P. fossulum indicates that while bothgenera are valid, the families are not justified. Brankocleistostoma is a dotillid; while Lazarocleistostoma is a varunid(subfamily Gaeticinae). The tribe Gopkittisakini Števčić, 2011 (type genus Gopkittisak Naruse & Clark, 2009), is also shown to be a junior synonym of Gaeticinae.